Guidance law to control impact angle and time based on optimality of error dynamics. (August 2019) - Li, Bin; Lin, Defu; Wang, Jiang; Tian, Song
In this work, a new guidance law with a meaningful performance index is designed to satisfy terminal impact angle and impact time constraints based on optimal error dynamics, which can be used for salvo attacks or cooperative missions of multi-missile. The analytical solution of the proposed guidance law is a combination of trajectory shaping guidance law and an additional impact time error feedback term that is proportional to the difference between the desired and the true impact times. Trajectory shaping guidance law aims to achieve the desired terminal impact angle and zero miss distance, whereas the extra term aims to meet the desired impact time. The minimum and maximum feasible impact times that consider the seeker's field-of-view limit, terminal impact angle constraint, and missile's maneuvering acceleration limit are calculated to provide the feasible boundary range of the desired impact time. Numerical simulations of several engagement situations demonstrate the effectiveness of the proposed guidance law in the accuracy of terminal impact angle and impact time.